Water-soluble nickel-bis(dithiolene) complexes as photothermal agents. Issue 25 (21st November 2014) - Mebrouk, Kenny; Chotard, Florian; Goff-Gaillard, Catherine Le; Arlot-Bonnemains, Yannick; Fourmigué, Marc; Camerel, Franck
Abstract : Pegylated nickel-bis(dithiolene) complexes can efficiently convert NIR light into heat in water to induce cell death. Abstract : The remarkable photothermal properties of pegylated nickel-bis(dithiolene) complexes in water can induce cell death under laser irradiation in the near infrared (NIR) region.